2008
DOI: 10.1158/0008-5472.can-07-2429
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Tolerance Associated with Prostate Cancer Is Independent from CD4+CD25+ Regulatory T Cells

Abstract: CD4 + CD25 + Foxp3 + regulatory T cells (Treg) are thought to suppress the natural and vaccine-induced immune response against tumor-associated antigens (TAA). Here, we show that Treg accumulate in tumors and tumor-draining lymph nodes of aging transgenic adenocarcinoma of the mouse prostate (TRAMP) male mice, which spontaneously develop prostate cancer. TAA overexpression and disease progression associate also with induction of TAA-specific tolerance. TAA-specific T cells were found in the lymphoid organs of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 46 publications
6
56
1
Order By: Relevance
“…28 An anti-CD25 Ab (PC 61) was used to deplete regulatory T cells from mice at 24 hours before LPS/D-GalN injection. 29 Cytochalasin B, a blocker of microfilament formation, was used to inhibit phagocytosis of macrophages and DCs. 30 For adoptive cell transfer, mice were treated with GdCl 3 , and then received portal vein (p.v.)…”
Section: Methodsmentioning
confidence: 99%
“…28 An anti-CD25 Ab (PC 61) was used to deplete regulatory T cells from mice at 24 hours before LPS/D-GalN injection. 29 Cytochalasin B, a blocker of microfilament formation, was used to inhibit phagocytosis of macrophages and DCs. 30 For adoptive cell transfer, mice were treated with GdCl 3 , and then received portal vein (p.v.)…”
Section: Methodsmentioning
confidence: 99%
“…8A) and autopsy (not shown) did not evidence sign of drug-related toxicity. At microscopic examination, the prostate of most of the vehicle-treated animals was characterized by enlarged acini presenting a well-differentiated microinvasive PC (33). The average disease score for these animals was 3.5 AE 0.71 (Supplementary Fig.…”
Section: Gr1mentioning
confidence: 99%
“…It has been suggested that Tregs especially hamper the breakthrough of most anticancer vaccination approaches [97]. On the other hand, TAA-specific T-cell tolerance being independent on Treg participation has been demonstrated by depletion experiments of the CD4 + CD25 + population in vivo in mice [98]. Even if the role of Tregs is not ultimately clear, evidence that they might be exploited by reprogramming represents an intriguing concept.…”
Section: The Principle Of Mimotope Vaccinesmentioning
confidence: 99%